Effect of Salicylic Acid on Growth and Bulb Yield of Onion (Allium Cepa L.) - Pradhan, M.; Tripathy, P.; Mandal, P.; Sahoo, B. B.; Pradhan, R.; Mishra, S. P.; Mishra, H. N. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted under All India Network Research Project on Onion and Garlic operating at College of Horticulture (OUAT), Sambalpur, Odisha India during winter season of 2013–14 to study the efficacy of exogenous application of salicylic acid (SA) on growth and yield in onion var. Agrifound Light Red. The experiment was laid out in RBD with four replication having six treatments of different sprays of SA including control. The results revealed exogenous application of SA significantly increased the better vegetative growth in terms of plant height (68.18 to 71.08 cm), collar thickness (16.90 to 18.51 mm) with higher level of chlorophyll content of leaves (31.53 to 33.01 SPAD) than untreated control (61.71 cm, 15.29 mm, 26.77 SPAD, respectively). Further among different times of SA application, foliar spray of SA at 30 days after sowing (DAS) in nursery, 30 and 45 or 60 days after transplanting (DAT) recorded significantly maximum vegetative parameters than rest of spray schedule. Similar trend was also recorded for bulb yield and yield attributing parameters. Spraying of SA at 3 times had better efficacy than 2 times of spraying in terms of bulb diameter (polar: 65.60 to 67.94 mm and equitorial: 49.10 to 49.80 mm), bulb weight (59.50 to 69.25 g), marketable bulb yield (180.91 to 183.10 qha-1) and total bulb yield (266.99 to 290.91 q ha-1). Hence, it may be concluded that application of SA at 30 DAS, 30 DAT and/ or 45 or 60 DAT not only increased the vegetative growth but also bulb yield in onion variety ALR.